ANALISIS IMAJI PADA ANTOLOGI PUISI VARIASI KUNING KUNYIT KARYA PENYAIR PEREMPUAN JAWA BARAT - Rahmat, Yati Syalwati; Dindin M. Z. M.; Desti Fatin Fauziyyah (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
Abstract This research uses qualitative descriptive methods. Data is taken from the words or sentences and expressions included in the images in the poetic anthology book Variasi Kuning Kunyit by the West Java female poet. Through poetry, a poet can express the bad and good things he feels so that every reader can feel the meaning of the poetry he reads. Based on this, the author researched the elements of the image in the poetic anthology book Variasi Kuning Kunyit by the West Java Woman Poet. With the data used of 94 poems belonging to 20 Western Java female poets, 366 image elements were obtained in them with visual and motion images that were more dominant. Keywords: Images, Anthology of Poetry.